Strategi Peningkatan Kapasitas Fungsional Pada Komunitas Osteoartitis Genu Dengan Latihan Fisik Di Wilayah Puskesmas Pajang Surakarta - Ahmad Najib Ali Ziyan; Farid Rahman; Kusdwi Hastuti (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Pajang is a locality in Kota Surakarta's Kecamatan Laweyan. Osteoarthritis is the most prevalent lansia disease in Kelurahan Pajang. Osteoarthritis lutut is a degenerative condition that affects the persendian that affects the kartilago, lapisan sendi, ligamen, and tulang such that it can cause nyeri and kekakuan in the sendi. The goals of a physical therapy program for osteoarthritis are to educate patients and demonstrate exercise therapy to improve nyeri and slow the progression of keluhan. This method employs teaching, demonstration, and penyuluhan (ceramah and tanya jawab) methods to discuss exercise regimens for osteoarthritis with Posyandu Lansia Mawar's consent. After providing education in physical therapy and demonstrating therapeutic techniques, the results included the discovery of any keluhan nyeri lutut on the lansia. We anticipate that the outcomes of this initiative to provide feedback to the public will serve as a benchmark for other professions in physical therapy or other fields of health care.